The Influence Of Talent Management On Organizational Performance With The Mediating Variable Of Employee Satisfaction And Employee Engagement At 4-Star Hotels In Batam City - Riny Mariany; Agustinus Setyawan (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the factors that affect organizational performance, especially the effect of talent management on organizational performance and the role of employee satisfaction and employee engagement as mediation. This research also uses quantitative methods based on questionnaire data collection distributed through the google form platform to 240 respondents in three 4-star hotels in Batam City and processed using SmartPLS 4 software. The results of this study prove that talent management significantly positively affects employee satisfaction and employee engagement. In addition, employee satisfaction and employee engagement variables significantly positively affect organizational performance. While the results of the indirect effect test also prove that the mediating variables of employee satisfaction and employee engagement significantly positively affect talent management on organizational performance.